Утилізація сульфідних стоків шляхом використання їх як сировини для виробництва натрія тіосульфату та колоїдної сірки - Ріпак, Назарій; Мальований, М. С. (Видавництво Львівської політехніки, 2013)
Industrial waste water contaminated with sulfide compounds formed in the chemical and refining processes, which are widespread in Ukraine . One of the methods of disposal of sulfide waste is using them as raw material for the production of sodium thiosulfate and colloidal sulfur. In the case of technology solutions polysulfide oxidation by atmospheric oxygen , may obtain both the above products. Experimental study of the oxidation of sodium polysulfide solution in a laboratory flotation machine on which found that results from the process of sulfur colloid meet essential quality parameters , making it possible to offer the principal technological scheme of this method of waste disposal sulfide.
Keywords: натрія сульфіди; натрія полісульфіди; сірколужні стоки; флотація; флотомашина; сірковмісні сполуки